2014
DOI: 10.3354/ame01720
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the role of viruses in marine nutrient cycling: bacterial uptake of D- and L-amino acids released by viral lysis

Abstract: Lysis of marine bacteria by viruses releases a range of organic compounds into the environment, including D-and L-amino acids, but the uptake of these compounds by other bacteria is not well characterized. This study determined that Photobacterium sp. strain SKA34 (Gammaproteobacteria) increased in abundance following uptake of D-and L-amino acids from viral lysate of Cellulophaga sp. strain MM#3 (Flavobacteria). Ammonium and dissolved free amino acids were taken up almost to detection limits, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The same could be said for the nutrients, except for particulate phosphorus, for which significant changes occurred with a significant increase and decrease in the VA+ and VA/VA− treatments, respectively. It was, however, difficult to establish a clear association between the viral and nutrient dynamics, while recent studies have demonstrated the importance of the viruses in producing dissolved organic matter or inorganic nutrients through cell lysis and their use by non-infected populations ( Shelford et al, 2012 , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same could be said for the nutrients, except for particulate phosphorus, for which significant changes occurred with a significant increase and decrease in the VA+ and VA/VA− treatments, respectively. It was, however, difficult to establish a clear association between the viral and nutrient dynamics, while recent studies have demonstrated the importance of the viruses in producing dissolved organic matter or inorganic nutrients through cell lysis and their use by non-infected populations ( Shelford et al, 2012 , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Dean et al (2008) revealed that bacterial lysis by viruses in Lake Erie could release fairly large quantities of phosphorus each day, suggesting a major role in the recycling of phosphorus. Currently, there is no longer any doubt that the virus-induced influx of organic matter can enhance bacterial production and fuels the microbial loop and the cycling of inorganic nutrients (see Shelford et al, 2014 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The net effect of the so‐called ‘viral loop’ is that it ultimately converts organic matter into dissolved inorganic nutrients, including respired CO 2 (Wilhelm & Suttle, ; Haaber & Middelboe, ; Pollard & Ducklow, ). Studies with marine microorganisms have revealed that viruses can be key players in nitrogen cycling (Haaber & Middelboe, ; Shelford et al ., ). In culture experiments, phage infection alters both host metabolism and lysate composition (Weinbauer & Peduzzi, ; Ankrah et al ., ; Sheik et al ., ).…”
Section: Viral Impact On Water Biochemistry and Carbon Flowmentioning
confidence: 97%
“…In the river‐influenced False Creek (Vancouver, Canada), experiments demonstrated that viral lysis leads to ammonium production from liberation of dissolved organic N that is re‐mineralised by uninfected bacteria, thus fuelling primary production (Shelford et al ., ). Nonetheless, a net uptake of ammonium by non‐infected bacteria in other culture experiments revealed that the metabolism of viral lysates can also result in net consumption of inorganic N (Shelford et al ., ). This recent evidence suggests that viral lysis of microbes changes the relative distribution of dissolved organic (and also inorganic) matter with many indirect effects on the aquatic systems (Weitz & Wilhelm, ).…”
Section: Viral Impact On Water Biochemistry and Carbon Flowmentioning
confidence: 97%
“…The microbial utilization of D -amino acids has been studied mainly in soils and is regarded as common in soil microorganisms (e.g., Hill et al, 2011 ; Broughton et al, 2015 ; Radkov et al, 2016 ). D -amino acid utilization by marine microbiota has also been studied (e.g., Perez et al, 2003 ; Azúa et al, 2014 ; Shelford et al, 2014 ); however, only a few D -amino acid utilizers have been isolated. As a deep-sea strain, Phaeobacter sp.…”
Section: Introductionmentioning
confidence: 99%